Analysis of The Implementation of Sharia-Based Digital Accounting - Binti Aulia Asfiati (IJCRE - International Journal of Culture, Religion, and Education, 2026)
This study aims to analyze the implementation of Sharia based digital accounting among Micro, Small, and Medium Enterprises (MSMEs) operating in Ngemplak Traditional Market, Tulungagung, and to identify the factors influencing its level of adoption. The research is motivated by the low use of digital financial recording systems that apply Sharia principles such as amanah, honesty, transparency or tabligh, and justice or adl. Sharia compliant digital accounting has the potential to improve efficiency, accountability, and the overall barakah or blessing in business management.A descriptive qualitative approach was employed, using observation, in-depth interviews, and documentation with ten purposively selected MSME actors. The findings indicate that the adoption of Sharia-based digital accounting remains low and varies based on age, education level, understanding of Sharia principles, and digital literacy. The main challenges include limited technological skills, insufficient knowledge of Sharia accounting, and resistance to shifting from manual bookkeeping habits. On the other hand, the key driving factors include the perceived benefits of digital applications, support from peer communities, and training programs provided by local government agencies and Sharia-oriented institutions.The study concludes that implementing Sharia-based digital accounting is not merely a technological matter but also a social, cultural, and spiritual process that requires stronger literacy, continuous assistance, and proper understanding of Islamic financial ethics tailored to local characteristics. The findings are expected to contribute to the development of Islamic Accounting and Finance studies and support an ethical, Sharia-compliant digital transformation for MSMEs in Indonesia.